2011
DOI: 10.3945/ajcn.110.006189
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of the fatty acid desaturase gene cluster predict amounts of red blood cell docosahexaenoic and other polyunsaturated fatty acids in pregnant women: findings from the Avon Longitudinal Study of Parents and Children

Abstract: FADS genotypes influence DHA amounts in maternal RBC phospholipids and might affect the child's DHA supply during pregnancy. It is highly likely that a gene product of FADS3 has a desaturating activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(148 citation statements)
references
References 47 publications
11
133
3
1
Order By: Relevance
“…Similarly, our current study and previous investigations in Western populations ( 3,5,8,10,40 ) consistently demonstrated that genetic variants in FADS1 gene were most signifi cantly associated with lower levels of 20:4n-6 ( ␤ = Ϫ 0.92) and EPA ( ␤ = Ϫ 0.04), but not with downstream fatty acids, such as DHA and 22:5n-6, in general populations. On the other hand, FADS1 rs174561 was associated with DHA in plasma phospholipids and human milk among 309 pregnant women ( 7 ), whereas signifi cant associations between erythrocyte DHA and FADS1 rs174548, rs174556, and rs174561 were also observed in 4,457 pregnant women ( 4 ). The discrepancy between our study and and fi sh intake on HDL cholesterol ( P for interaction = 0.08) (supplementary Table IV).…”
Section: Genotypingcontrasting
confidence: 57%
“…Similarly, our current study and previous investigations in Western populations ( 3,5,8,10,40 ) consistently demonstrated that genetic variants in FADS1 gene were most signifi cantly associated with lower levels of 20:4n-6 ( ␤ = Ϫ 0.92) and EPA ( ␤ = Ϫ 0.04), but not with downstream fatty acids, such as DHA and 22:5n-6, in general populations. On the other hand, FADS1 rs174561 was associated with DHA in plasma phospholipids and human milk among 309 pregnant women ( 7 ), whereas signifi cant associations between erythrocyte DHA and FADS1 rs174548, rs174556, and rs174561 were also observed in 4,457 pregnant women ( 4 ). The discrepancy between our study and and fi sh intake on HDL cholesterol ( P for interaction = 0.08) (supplementary Table IV).…”
Section: Genotypingcontrasting
confidence: 57%
“…These long-chain polyunsaturated fatty acids (LC-PUFAs) accumulate in the brain in abundance from the third trimester to 18 months postpartum and are essential for neurogenesis, neurotransmission, and protection from oxidative stress. [51][52][53] The candidacy of FADS2 as a risk modulator for preterm brain injury is raised because FADS2 gene variants have functional effects on LC-PUFA availability, with minor allele carriage at common SNPs including rs174576 being associated with altered levels of arachidonic acid and docosohexaeneoic acid in phospholipid, serum, and breast milk, [54][55][56][57][58] and FADS2 variants may interact with early dietary exposures to influence childhood IQ. 34,35 We found that minor allele carriage at rs174576 is associated with lower FA in white matter, after controlling for nongenetic confounders.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, the expression of the FADS3 transcripts was upregulated by dietary long-chain PUFAs, whereas FADS1 and FADS2 mRNA levels were decreased ( 17 ). In addition, gene polymorphism studies carried out in humans showed that several single nucleotide polymorphisms (SNP) located within the FADS3 gene were associated with variations in triglycerides, HDL-and LDL-cholesterol plasma levels ( 18,19 ), and with variations in plasma PUFA levels (20)(21)(22)(23). These correlations underlined the possible implication of FADS3 in lipid and FA homeostasis.…”
Section: Fatty Acid Analysismentioning
confidence: 99%